IMPLEMENTASI SISTEM INFORMASI DESA BOGATAMA BERBASIS WEBSITE OPENSID - Maulana, Affan (Fakultas Teknik, Universitas Bangka Belitung, 2024)
In the context of globalization, technological advancements progress rapidly, facilitated significantly by the swift dissemination of information. Websites have emerged as potent tools for data collection due to their extensive global reach. Specifically, developing a village website is a practical application of information technology. This website enables the prompt and efficient dissemination of information concerning village affairs, thus enhancing the accessibility of data on village activities and other previously unrecorded information. The primary objective of this system is to simplify the process of sharing critical information about the village, encompassing aspects like community activities, demographic details, geographical data, and local economic potentials. The research methodology includes observation, interviews, and a review of existing literature, which collectively aim to augment services provided to rural communities and promote the visibility of local enterprises and resources. The OpenSID module was utilized to construct this village information system, facilitating easier and quicker access to village services for residents. The inhabitants of Bogatama Village anticipate that this digital information system will significantly improve the quality of service delivery processes.